MICRORESEARCH ON ANTIMICROBIAL RESISTANCE IN TERTIARY CARE HOSPITAL OF ANDHRA PRADESH - SUBERNA BASNET; YALLASAI VIJAYA DURGA; ALLU TEJASWI; ALI NIHAL; BODDU DEVIKA; PENUGONDA VINEELA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: In this study, we aim to investigate the prevalence of antimicrobial resistance (AMR) in an isolated bacteria from the infected population admitted in a tertiary care hospital. By this, we can the evaluate resistance load and be aware of the future danger of antibiotic resistance. Methods: A descriptive study was conducted on a total of 127 patients admitted to tertiary care hospitals of Andhra Pradesh between September 2023 and April 2024, respectively. Bacteria isolated were tested for antibiotic resistance with 13 different antibiotics by disk diffusion methods. A comparative analysis was performed to identify the differences in resistance rate among the bacterial strains and observed the multiple antibiotic resistance load in the individual bacteria. Results: Our descriptive analysis reveals varying degrees of antibiotic resistance in the organisms we studied. Twenty-seven of the 127 samples, we had in total had no evidence of bacterial resistance. In the specific sample area we used, the prevalence of antibiotic resistance was 78.7%, with amoxicillin having the highest rate of resistance at almost 55%, and the Chi-square test’s p=0.001 showed a strong correlation between antibiotic resistance and bacteria isolated. Conclusion: Our finding revels that there is increasing AMR load in South India district. Those resistance reports indicate the urgent need of antimicrobial stewardship coordination program and start the surveillance program to combat the antibiotic resistance on the general population. Furthermore, microsurveillance should be conducted in every district to detect antibiotic resistance load and develop new treatment strategies.